Single-shot technique of cryoablation for atrial fibrillation has comparable effective and safety outcomes compared to standard technique: insights from multiple clinical studies - He, Changjian; Zhang, Wenchang; Yin, Lei; Sun, Mingzhuang; Zhao, Zihan; Ye, Guojie; Liu, Tengfei; Shi, Wence; Zhang, Da; Li, Feng; Ding, Chunhua (Frontiers in Cardiovascular Medicine, 2023)
Background: Although there are many freezing protocols available, the optimal freezing dose is still not determined. We aimed to evaluate the effectiveness and safety of different freeze strategies of CBA in the treatment of AF.: PubMed, Cochrane Library, Web of Science, and Embase were searched up to 1st December 2022. Studies comparing the outcomes between single-shot technique and standard technique of cryoablation were included. Subgroup analysis identified potential determinants for single-shot technique procedure. Results: Our search resulted in 3407 records after deduplication. A total of 17 qualified studies met our inclusion criteria. Compared with standard technique, single-shot technique of cryoablation has a comparable rate of freedom from AF/AT(RR 1.00; P=0.968) , a trend for lower rate of procedure complications (RR 0.80; P= 0.069), a lower rate in transient phrenic paralysis (t-PNP) (RR 0.67; P=0.038), a similar rate in persistent phrenic paralysis (per-PNP) (RR 1.15; P=0.645),as well as a comparable procedure parameters. Importantly, potentially significant treatment covariable interactions in procedure complications were found in freeze strategy subgroup, male proportion subgroup and age subgroup, including single-shot freeze (RR 1.02; P=0.915) and TTI-guided (RR 0.63; P=0.007) with interaction P=0.051, high male proportion (RR 0.54; P=0.005) and a low male proportion (RR 0.94; P=0.759) with interaction P=0.074, as well as age≥65 (RR0.91; P=0.642) and age<65 (RR 0.54; P=0.006),interaction P=0.090. Meanwhile, only one significant treatment covariable interactions in procedure complications was found in the hypertension subgroup, including HT>60% (RR 0.89; P=0.549) and HT ≤ 60% (RR 0. 4 46; P<0.01) with interaction P=0.043. Conclusions: Our study suggested that single-shot technique of cryoablation has comparable effective and safety outcomes for AF ablation compared to standard technique.